Morphological and Quantitative Characteristics of the Skin of Holstein Cattle in the Amur Region - E. Ostyakova, ÐœarinÐ°; Yu. Sayapina, Irina; Nikolay M. Mandro, Nikolay; V. Trush, Natal'ya; A. Gavrilov, Yuriy; A. Gavrilova, Galina; V. Hibchenov, Lopsondorzho; N. Chubin, Alexey (International Journal of Engineering and Technology, 2018)
The skin of mammals has a high reactivity to the conditions of the external and internal environment. There is no information about the features of the structure of the skin of Holstein cattle in the context of its adaptation to the sharply continental with the symptoms of monsoon climate in the available literature. The purpose of the study was to determine the structural features of the skin of the sternal and costal regions of cattle of the Holstein breed in the Amur region. For the study, the skin of clinically healthy mature Holstein cows was taken. Time of research - autumn. The skin was fixed in a 10% aqueous solution of neutral formalin. Paraffin sections with a thickness of 5-7 Î¼m were prepared. The sections were stained with hematoxylin and eosin, collagen fibers were detected by the Van Gison method, elastic fibers by Weygert. A distinctive feature of the papillary layer of the dermis was a well-developed system of venous sinuses that anastomosed with each other. The abundance of mononuclear cells in the lumen of the sinuses indicated the important role of the skin as an organ of the immune system that provides adaptation and protection of animals in a sharply continental climate.Â